SOME OBSERVATIONS ON THE CULTURE OF THE AIRBREATHING FISH CHANNA STRIATA (BLOCH) IN FARM PONDS - Ravindranath, K (Indian Journal of Fisheries, 2011)
The air-breathing fish Channa striata (Bloch), commonly called the striped murrel (snake-head) is one of the most sought-after freshwater fishes in several parts of India. While snake-heads (Channa spp.) are cultured in cages and ponds in some of the South-East Asian countries